Propeller effects on energy, exergy and sustainability parameters of a small turboprop engine - Aygun, Hakan; Kirmizi, Mehmet; Turan, Onder (Pergamon-Elsevier Science Ltd, 2022)
Turboprop engines have been commonly adopted for several applications such as unmanned aerial vehicle and commuter aircraft. In this study, the effects of propeller efficiency (PEF) with various compressor pressure ratio (CPR) are examined for energetic, exergetic, environmental and sustainability indicators of a small turboprop engine (S-TPE) at sea level. For this aim, PEF of the S-TPE has the range varying between 0.7 and 0.95 whereas its CPR has boundary changing between 10 and 12.5. According to performance results, thrust of the S-TPE changes from 5.11 kN to 6.88 kN due to rising PEF and from diminishes from 5.9 kN to 5.68 kN due to rising CPR whereas overall efficiency of the S-TPE alters from 22.1% to 29.7% owing to the PEF effect and from 24.7% to 25.5% owing to the CPR effect. On the other hand, exergetic parameters of the components of the engine remain constant with the PEF effect whereas both effects (PEF and CPR) are observed on exergetic metrics of the whole engine. In this context, exergy efficiency of the combustor increases from 84.83% to 86.7% due to only the CPR effect. Moreover, exergy efficiency of the S-TPE experiences the increase from 21.39% to 28.77% due to rising PEF while it raises from 23.99% to 24.71% due to rising CPR. Finally, specific wasted exergy of the S-TPE decreases from 0.7566 MW/kN to 0.5624 MW/kN with the effect of PEF whereas it drops from 0.6751 MW/kN to 0.6540 MW/kN with the effect of CPR. These findings show that a small change in design variables reflects on energetic and exergetic performance of the engine at different degrees.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Energy; Propeller efficiency; Compressor; Turboprop; exergy